The effect of channel dimensions and configuration of thermoelectric elements on the performance of thermoelectric generator module for waste heat recovery. (April 2023) - Ghoreishi, Zhiaveh; Khalilarya, Shahram; Jafarmadar, Samad
Highlights: Temperature difference between the two sides of thermoelectric generators is an effective factor. Temperature-dependent thermoelectric properties are assumed. Optimal dimensions of the channel are obtained based on the maximum power. There are minimum dimensions of the channel to produce the power of thermoelectric generation module. Changing the water flow regime from turbulent to laminar reduces the power and efficiency of the thermoelectric generator module. Abstract: The use of thermoelectric modules can be effective in recovering waste heat in combustion gasses due to their special properties. In this study, due to the low efficiency of thermoelectric generators, the effects of channel dimensions and configuration of thermoelectric element pairs on heat transfer between a working fluid and a pair of PN elements were studied horizontally and vertically. To develop the simulation of the present model, temperature dependence of generator properties, variations in the convective heat transfer coefficient, temperature gradient, and pressure drop in both hot and cold working fluids along the channel were considered simultaneously. Additionally, it was found that geometric dimensions of rectangular channels affected the four main factors of temperature difference between the two sides of generators, pumped power, number of generators, and type of flow regime. Besides, the findings revealed that the increase in each dimension of the channel reduced the temperature difference between the two sides of elements. This factor was found to play a major role in the efficiency of the thermoelectric generator device, production of power peak, optimal module, channel area, and optimal channel height. In addition, the flow regime changed from turbulent to laminar at cold channel widths greater than 0.11 m. As a result, the total power dropped. Furthermore, the configuration model of PN elements affected the dimensions of the channel. At the length of 1.275 m of the channel, the power generation capacity of the vertical model was by 2.138 times greater than that of the horizontal model per 100 thermoelectric generators.